Estudo de previsão de demanda aplicado à gestão de estoque de insumos em uma empresa de beneficiamento de palmito - ALFAIA, Rodrigo de Almeida (2022)
This work deals with the analysis of the current situation of the company studied, finding the problem to be focus of the work and the choice of important tools for planning and control needed to treat it. Through a bibliographical research was used the theoretical knowledge to the application of it in practice. The approach used was a case study, which dealt investigate and evaluate the company's operations with gathering information and finding noncompliance to be worked. After such a definition were tested and applied demand forecasting methods from these collected data, thus subsidizing other inventory control tools that helped to measure acceptable levels of stored materials and quantities to be purchased, as well as the range time that this purchase should be requested. Thus, studies have been adapted to the reality of the company, becoming effective and necessary to the effectiveness of materials management, reducing costs arising from losses and stoppages in production and material waste.